1982
DOI: 10.1177/00220345820610121401
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Prostaglandins on Experimental Tooth Movement in Monkeys (Macaca fuscata)

Abstract: Local administrations of prostaglandins E1 or E2 combined with orthodontic tooth movement can approximately double the rate of tooth movement in monkeys compared to that of the control. Macroscopically, no side-effect was observed in the gingiva and associated structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0
7

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(72 citation statements)
references
References 7 publications
1
64
0
7
Order By: Relevance
“…They found a significant increase in the rate of tooth movement and number of osteoclasts present after local administration of osteocalcin in rats compared to controls that only received administration of phosphate-buffered saline (PBS). Yamasaki et al 48,49 similarly showed an increase in the rate of tooth movement after local administration of prostaglandin E1, a biochemical mediator of bone resorption in both monkeys and humans.…”
Section: Effect Of Bone Remodeling Rates and Density On Tooth Movementmentioning
confidence: 98%
“…They found a significant increase in the rate of tooth movement and number of osteoclasts present after local administration of osteocalcin in rats compared to controls that only received administration of phosphate-buffered saline (PBS). Yamasaki et al 48,49 similarly showed an increase in the rate of tooth movement after local administration of prostaglandin E1, a biochemical mediator of bone resorption in both monkeys and humans.…”
Section: Effect Of Bone Remodeling Rates and Density On Tooth Movementmentioning
confidence: 98%
“…In orthodontics, there seems to be a consensus on the fact that PGE2 injections increase the rate of tooth movement (Bao, Zhao & Rao, 1995;Chao et al, 1988;Kale et al, 2004;Kokkinos et al, 1993;Leiker et al, 1995;Seifi, Eslami & Saffar, 2003). In contrast to orthopedic studies, which typically show anabolic effects of PGE2 (Norrdin, Jee & High, 1990), studies have reported increase in bone resorption alone (Boekenoogen et al, 1996;Chao et al, 1988;Kale et al, 2004;Leiker et al, 1995;Seifi et al, 2003;Yamasaki, Shibata & Fukuhara, 1982). For ERR, there are studies that report an increase (Boekenoogen et al, 1996;Leiker et al, 1995), but there are also studies that report no significant effect of this molecule (Brudvik & Rygh, 1991).…”
Section: Biological Factors In Rate Of Tooth Movement and Errmentioning
confidence: 99%
“…The biomechanical methods involve medicine such as prostaglandin E2, a parathyroid hormone. 1,2 Biostimulation involves the modification of the environment to stimulate existing bacteria capable of bioremediation. With the introduction of therapeutic lasers, biostimulation also refers to the application of photon energy to injured tissue, in order to achieve a stimulatory and regenerative effect at the molecular level.…”
Section: Introductionmentioning
confidence: 99%